Zwolnienie od podatku od czynności cywilnoprawnych sprzedaży gospodarstwa rolnego jako forma pomocy de minimis w rolnictwie - Trela, Anna (Wydawnictwo Naukowe UAM, 2017)
This paper analyses the regulation of Article 9 point 2 of the Act of 9 September 2000 on the tax civil law transactions (CLT). The said provision applies to the exemption from the sales tax if the object of sale is a farm holding or a property included in a farm holding. The amendments of 2015 to the above mentioned Act added a sentence which provides that “such exemption constitutes a de minimis help in agriculture referred to in Regulation EC No 1408/2013 of 18 December 2013 concerning the application of Articles 107 and 108 of the Treaty on the Functioning of the European Union regarding the de minimis help in the agricultural sector”. This new wording of Article 9 point 2 of the Act on CLT has entailed many doubts regarding the allowable level of exemption, the principles of its calculation and recovery. Hence the need to analyse the relevant legal provisions of the EC Regulation. In the author’s opinion the Regulation contains no provision stating that if the combined sum of help exceeds the predetermined ceiling it will be exempted from the provision, even if only up to the level not exceeding the ceiling. Under the current provisions the de minimis help in agriculture may not exceed EUR 15 000, also in the event referred to in Article 9 point 2 of the Act on CLT. Due to the lack of consistent legal provisions regarding tax exemptions, the authoress decided to present in the article other instruments available under Polish law, which provide for the de minimis help in agriculture.
Exemption from tax on the sale of a farm holding as a form of a de minimis help in agriculture
Keywords: tax exemption; tax; farm holding; de minimis help in agriculture; Regulation EC No 1408/2013